Regional Elections Conducted by the Regional People’s Representative Council and the Shifting Meaning of People’s Sovereignty in Political Communication Analysis - Wisnu Budiaji; Moh. Mahshun Al Fuadi (Publikasi Indonesia, 2026)
This study examines the discourse on the election of regional heads by local legislatures and its implications for the shifting meaning of popular sovereignty in Indonesian democracy. The research is motivated by the reemergence of proposals for indirect local elections, which raise constitutional, sociological, and political debates. The research problem focused on how changes in the electoral mechanism affect the relationship between popular will, political legitimacy, and political communication practices. This study employs a qualitative approach through a literature review of academic works, legal regulations, and Constitutional Court decisions. The analysis applies Jean-Jacques Rousseau’s theory of popular sovereignty, Carole Pateman’s participatory democracy, and Dan Nimmo’s political communication theory. The findings indicate that elections conducted by local legislatures tend to strengthen elite-driven democracy, reduce direct citizen participation, and shift political legitimacy toward political elites. The study concludes that this transformation narrows the substantive meaning of popular sovereignty in local democratic practices.